2013
DOI: 10.4314/gjass.v11i2.1
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Assessment of Protected area Pressures and Threats in Nigeria National Parks

Abstract: Regular evaluation of protected area operations can enable policy makers develop strategic responses to pervasive management problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
0
5
0
1
Order By: Relevance
“…The main purpose of the RAPPAM methodology is to increase and improve the conservation of protected areas both of individual sites and the protected area system (Nepali 2006). The RAPPAM questionnaire is also an important part of the tool as it covers all the aspects of the international evaluation framework developed by the WCPA (Nchor & Ogogo 2012). The questionnaire is divided into seven sets of which the first set deals with the basic information about the Protected Areas including the management objectives and activities.…”
Section: Discussionmentioning
confidence: 99%
“…The main purpose of the RAPPAM methodology is to increase and improve the conservation of protected areas both of individual sites and the protected area system (Nepali 2006). The RAPPAM questionnaire is also an important part of the tool as it covers all the aspects of the international evaluation framework developed by the WCPA (Nchor & Ogogo 2012). The questionnaire is divided into seven sets of which the first set deals with the basic information about the Protected Areas including the management objectives and activities.…”
Section: Discussionmentioning
confidence: 99%
“…While the NGSA 1 reflects its conservation and restricted use status, the additional association of NGSA 1 with high and rugged elevations like NGSA 9, further explains its small extent of degradation. However, with its low proximity to major roads and major towns, degradation in protected areas as captured in NGSA 1 call for an investigation into the specific activities driving degradation in protected areas, such as encroachment by human activities [11,63], despite government regulations, particularly around communities that host protected areas [67,68].…”
Section: Understanding the Archetypes Of Small-area Degradationmentioning
confidence: 99%
“…Overgrazing has been associated with the disappearance of the typical savannah vegetation and the emergence of the Sudan-Sahelian Savannah in the NGS [15,72]. Thus, from the combination of drivers above, there is a critical need for an improved management of grazing resources, protected areas, and the governance of land resources in the NGS [11,36,68]. While all small-area archetypes are mostly dominated by the land-use management drivers, NGSAs 6 and 8 are the only small-area archetypes that are distinctly driven by the socio-economic drivers characterized by areas with low population density, i.e rural population with corresponding moderate information/knowledge access.…”
Section: Understanding the Archetypes Of Small-area Degradationmentioning
confidence: 99%
“…In a study performed for rapid evaluation of the pressure factors in protected areas along with the threat factors in national parks, the greatest threat factors of national parks were related to grazing, hunting, harvest of timber trees, and fishing. These threat and pressure factors are directly related to the vulnerability of the area (Nchor et al, 2012). In a study dealing with analysis of the threat and pressure factors in wetlands of South of Iran using RAPPAM method in Khuzestan Province (2014), it was found that extensive changes in land use into residential and agricultural uses, exhaustion and fracture of oil pipes and oil products in the wetland, legal and out of season hunting claimed the highest scores of pressure and threat factors, respectively (Sabzghabaei et al, 2014).…”
Section: Introductionmentioning
confidence: 99%